A new solution technique for cathodic protection systems with homogeneous region by the boundary element method. Issue 5 (2nd November 2018) - Santos, W. J.; Brasil, S. L. D. C.; Santiago, J. A. F.; Telles, J. C. F.
Abstract: The purpose of this work is to efficiently evaluate the design of cathodic protection (CP) systems of tank bottoms using concentric ring or linear anodes. As customary in current CP systems, the outer surface of the tank bottom is usually in electrical contact with a slender homogeneous layer of conductive concrete (or something similar) which in turn is in direct contact with the homogeneous deep soil region. The boundary element method (BEM) together with a subregion technique has been widely adopted to analyse such CP systems where the domain consists of two (or even more) homogeneous zones. However, the numerical solution of the final matrix system of equations can be quite time-consuming, especially if the slender intermediate layer is to be discretised, requiring a considerable number of elements, due to its somewhat reduced thickness. To overcome this problem, the present work proposes a new methodology in which the slender subregion is indirectly introduced, as a theoretically created polarisation curve, acting as a new boundary condition at the boundary of the soil domain (original common interface). Numerical simulations have been carried out using BEM implementations and results are discussed, including CP studies of practical axisymmetric and three-dimensional engineering problems.